Religious Moderation and Social Welfare: A Multidimensional Approach to Poverty Alleviation and Human Development - Ismail, Dailani; Rizal, Deri; Hizbi Islami, Muhammad; Azhari, Ari (MD Research Center, 2025)
This study discusses the role of religious moderation in the context of social welfare, focusing on a multidimensional approach to poverty alleviation and human development. In a pluralistic society, religious moderation becomes key to creating a harmonious and inclusive social environment. By promoting values of tolerance and mutual respect among religious groups, religious moderation can reduce social tensions and discrimination that hinder community empowerment. This research explores how the integration of religious moderation principles into social policies and development programs can create strong social networks, strengthen interfaith collaboration, and enhance community participation in economic empowerment initiatives. Religious moderation not only serves as a tool to reduce conflict but also as a driver of innovation in inclusive social policies that are responsive to marginalized groups. The study also identifies challenges in implementing religious moderation, such as resistance from certain groups and the still-present exclusive paradigms in society. Therefore, strengthening inclusive religious education and engaging religious leaders in intergroup dialogue is crucial to raising awareness about the importance of moderation in achieving social welfare. The findings show that a multidimensional approach involving religious moderation can accelerate poverty alleviation and improve human quality of life as a whole. The conclusion emphasizes the need for collaborative strategies involving the government, civil society organizations, and religious communities to achieve sustainable development goals.